Oral History Interview: Eunice Gibson (1704) - Gibson, Eunice (My University, 2018)
Interview about her time in Madison as an Undergraduate and Law School student. Upbringing, journey to Madison, time working for the Wisconsin Democratic Party, living in Panama, Law School, working at the City Attorney's Office and being the first female City Attorney for Madison.
Interviewed by: Emma Strenski
Keywords: Background; Undergraduate; Madison; City Attorney; UW-Madison; Law School